Dormancy breaking studies and seed germination in Arenga wightii Griﬃth - Jacob, Joemon; Chitra, C. R.; Anilkumar, C. (Journal of Plantation Crops, 2023)
Arenga wightii Griﬃth, an endemic palm, of Western Ghats and south and central Sahyadris having multiple uses is currently under threat due to habitat loss and over exploitation. Since seeds are the major propagules of this palm, seed study was carried out with a view to conserve this highly promising tree, in both ex-situ and in- situ conditions. The study included seed viability, germination, desiccation and dormancy breaking tests. The results of the study suggest desiccation, GA3/ acid treatment enhance germination, and dormancy observed is of both physiological and mechanical. The cost eﬃcient means of germination induction is desiccation which could aid the farmers and common people in cultivating the species at large extent enabling reintroduction of the species.